Can it ever be too early to introduce workplace wellness programs? - Nikraz, Ommid; Jansz, Janis; Gilroy, P. (Vertical Events, 2009)
Wellness' programs in today's workplaces are usually initiated to encourage mature employees to adopt healthier lifestyles. In many cases it is too late - the horse has already bolted. Little data is available on the persistence of the modified behaviours or the longitudinal benefits of the programs although there are reports of reduced sick leave, staff turnover and workers' compensation costs. Improved worker morale has been noted. With current life expectancy now exceeding 80 years and the prospect of today's teenagers working for some sixty years, it is critical that 'wellness' concepts be introduced at an early age if we are to thwart current epidemics of obesity, diabetes and other health related issues. We will simply be unable to meet the health costs of an increasingly aging work force. This paper offers some challenging suggestions as to how this much needed intervention could be achieved.